2019
DOI: 10.3892/ol.2019.10310
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‑1 and dynamin‑2 overexpression is associated with the progression of bladder cancer

Abstract: Caveolae-mediated endocytosis regulates cell adhesion and growth in an anchorage-dependent manner. Studies of the endocytic function of caveolae have suggested a wide-ranging list of cargoes, including a number of receptors and extracellular proteins, ligands and nutrients from the extracellular matrix. Disruption of the processes of caveolae-mediated endocytosis mediated by signaling proteins is critical to cellular integrity. Caveolin-1 and dynamin-2 are the 2 major proteins associated with endocytotic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…DNM2 is known for its role in endocytic cell trafficking and microtubule dynamics. High DNM2 expression is reported in bladder cancer [ 46 ], whereas Chernikova et al showed that levels of DNM2 could predict chemotherapy outcomes for triple-negative BrCa patients [ 47 ]. Another gene included in the signatures and found to be hypermethylated in early BrCa, SSH1 , has been presented to be a cancer progression factor [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNM2 is known for its role in endocytic cell trafficking and microtubule dynamics. High DNM2 expression is reported in bladder cancer [ 46 ], whereas Chernikova et al showed that levels of DNM2 could predict chemotherapy outcomes for triple-negative BrCa patients [ 47 ]. Another gene included in the signatures and found to be hypermethylated in early BrCa, SSH1 , has been presented to be a cancer progression factor [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that caveolin-1 was related to endocytosis, signaling and lipid disorders, while recent studies focused on clarifying its relevance in cancer. Caveolin-1 is expressed in esophageal carcinoma ( 19 , 20 ), prostate cancer ( 8 17 ), colon cancer ( 21 ), breast cancer ( 22 ), bladder cancer ( 23 ), lung cancer ( 24 ), and other cancers ( 25 , 26 ), and acts as a tumor promoter or suppressor. As a tumor promoter, high expression of caveolin-1 drives tumorigenesis by inhibiting apoptosis, facilitating anchorage-independent growth, drug resistance as well as metastasis ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several membrane proteins required for endocytosis become dysfunctional during cancer development, as is the case for CAV1. For instance, CAV1 and dynamin-2, which are both important for caveolamediated endocytosis and caveola assembly, are highly expressed in bladder cancer and possibly contribute to the progression of this type of cancer [134].…”
Section: Endocytosis and Autophagymentioning
confidence: 99%